Antonio Preciado-Bedoya's "Fundó un mar en el Chota": an interconnected Afro vision of Ecuador. Issue 2 (3rd May 2020) - Vargas Holguín, Elizabeth
ABSTRACT: The main aim of this article is to explore Antonio Preciado-Bedoya's poem "Fundó un mar en el Chota" from the collection De sol a sol (1992). In this poem, the poet depicts an interconnected understanding of the Afro experience in Ecuador. My article first explores the colonial political environment leading to the division between the Chota and Esmeraldas. Then I present an overview of the current Afro-Ecuadorian thematic trends that makes it possible to explore Preciado-Bedoya's own thematic interest in the themes of an interconnected Afro experience in Ecuador: that is, a shared intrahistoria ; the transplantation of goods with symbolic, material, and historical value; and the Afro voice of the Chota. I conclude by looking into the relational or ontological mechanism that makes possible the poetic connection that bridges the historically isolated regions of the Chota and Esmeraldas.